Grade 3 Severe Liver Injury Secondary to Pembrolizumab - López-Marte, Paola; Rosado-Carrión, Bárbara (Puerto Rico Health Sciences Journal, 2023)
Over the last years, pembrolizumab has been one of the checkpoint inhibitors that have revolutionized the management of unresectable malignancies given its successful rate of disease control. This drug has become part of the standard of care in several types of cancers, however, the side effects are an emerging concern for physicians managing patients with cancer. Immune mediated injury of these drugs can target virtually any organ. Liver injury is an important side effect of these drugs that can be life threatening and needs to be well recognized. Here we report a case of an 85-year-old male with medical history of stage 3 laryngeal carcinoma who presented with severe liver injury secondary to pembrolizumab.